Psychological Distress After Covid-19 Recovery: Reciprocal Effects With Temperament and Emotional Dysregulation. An Exploratory Study of Patients Over 60 Years of Age Assessed in a Post-acute Care Service - Janiri, Delfina; Kotzalidis, Georgios D.; Giuseppin, Giulia; Molinaro, Marzia; Modica, Marco; Montanari, Silvia; Terenzi, Beatrice; Carfì, Angelo; Landi, Francesco; Sani, Gabriele; , The Gemelli Against COVID-19 Post-acute Care Study Group (Frontiers in Psychiatry, 2020)
To study the long-term psychological effects of Covid-19 disease, we recruited 61 patients older than 60 years of age and administered the Kessler questionnaire K10 to assess psychological distress and classify them according to mental health risk groups. Patients’ affective temperaments were assessed with the 39-item form of the Temperament Evaluation of Memphis, Pisa, Paris and San Diego (TEMPS-A-39) and emotional dysregulation with the Difficulties in Emotion Regulation Scale (DERS). Patients were divided in two samples according to their scores on the K10, i.e., a high likelihood of psychological distress group (N=18) and a low likelihood of psychological distress group (N=43). The two groups differed on their gender composition, in that more women (N=11) were in the former and more men in the latter (N=29) (χ2=4.28; p=0.039). The high likelihood of psychological distress group scored higher on the Cyclothymic (3.39 ± 3.45 vs. 0.93 ± 1.08, p<0.001) and the Depressive (2.28 ± 2.82 vs. 0.65 ± 1.09, p=0.01) affective temperaments of the TEMPS and on the lack of Impulse control (12.67 ± 4.04 vs. 9.63 ± 3.14, p=0.003) and lack of Clarity (15.00 ± 5.56 vs. 9.85 ± 4.67, p=0.004) scales of the DERS. Our results show that having had Covid-19 may be related with high likelihood for psychological distress in advanced-age people and this may in turn be associated with impaired emotional regulation and higher scores on depressive and cyclothymic temperaments.